1980
DOI: 10.1063/1.438941
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of nucleation in binary mixtures: The methanol–water and n-propanol–water systems

Abstract: The upward diffusion cloud chamber was used to study the homogeneous nucleation of the MeOH–H2O and n-PrOH–H2O mixtures over a wide range of water activities (i.e., relative humidities). The results are compared with the predictions of theory. Good agreement between the experimental results and the classical theory of homogeneous nucleation was found for alcohol rich mixtures. However, at high water concentrations, the experiments require much more alcohol than theoretically predicted. This is the same conclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…(7) into Eq. (11 ) is the supersaturation and Psat is the saturation pressure at T. Having estimated t:..f.L in Eq. (4), we suggest a generalized phenomenological form for the difference Mi of Helmholtz free energies F j and if 00 as (it is well known that M; cannot totally be determined from thermodynamics or statistical mechanics)…”
Section: ( Iflu)mentioning
confidence: 99%
“…(7) into Eq. (11 ) is the supersaturation and Psat is the saturation pressure at T. Having estimated t:..f.L in Eq. (4), we suggest a generalized phenomenological form for the difference Mi of Helmholtz free energies F j and if 00 as (it is well known that M; cannot totally be determined from thermodynamics or statistical mechanics)…”
Section: ( Iflu)mentioning
confidence: 99%
“…Historically, the use of the classical homogeneous theory has successfully predicted critical activities of a number of pure systems and binary mixtures . However, very poor agreement with experiment has been found for nonideal mixtures. ,,, It was first Renninger et al and then Wilemski , who, in the early 1980s, showed that the classical theory was inconsistent when the surface tension of the system changes significantly with composition. Wilemski proposed a “revised classical theory” using the Gibbs adsorption equation, which takes into account surface-enrichment effects.…”
Section: Introductionmentioning
confidence: 99%
“…7 The experimental data on the composition dependence of the surface tension were fitted by the expression…”
Section: Numerical Evaluations For a Water-methanol Systemmentioning
confidence: 99%
“…1-4 Nevertheless, the development of an adequate macroscopic nucleation theory remains of great importance because it provides a simple and virtually universal formalism applicable to first-order phase transitions in most complex systems. 5,6 It has been known for quite a while that experimental data on the binary nucleation rate can differ by many orders of magnitude [7][8][9][10][11] from the predictions of binary classical nucleation theory ͑BCNT͒, based on the capillarity approximation. 6 As one possible explanation of these discrepancies, it was suggested 7 that such large discrepancies between BCNT and experiment are due to adsorption effects.…”
Section: Introductionmentioning
confidence: 99%